2011
DOI: 10.1029/2011jd015895
|View full text |Cite
|
Sign up to set email alerts
|

Computation of clear-air radar backscatter from numerical simulations of turbulence: 1. Numerical methods and evaluation of biases

Abstract: [1] A numerical simulation of secondary instability and turbulence accompanying Kelvin-Helmholtz shear instability and a numerical algorithm computing radar backscatter from these turbulence volumes are employed to examine the validity of routine assumptions employed in radar studies of atmospheric dynamics that rely on backscatter from refractive index fluctuations. The numerical simulation of KH instability describes turbulence dynamics and character from the onset of instability, through fully developed tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…A good contemporary review of the well-known biases inherent in volume-scatter-derived wind measurements in the presence of correlations between refractive index fluctuations and the underlying dynamics is provided by Fritts et al (2012c). This study used a numerical algorithm to compute off-zenith backscatter from simulated Kelvin-Helmholtz instabilities in the mesospheric region (Franke et al, 2011), and revealed the biases in the obtained Doppler spectra as a function of the stage of turbulence development. Simulation-based approaches like this clearly underpin future investigations of the validity of the partial reflection Doppler techniques employed in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…A good contemporary review of the well-known biases inherent in volume-scatter-derived wind measurements in the presence of correlations between refractive index fluctuations and the underlying dynamics is provided by Fritts et al (2012c). This study used a numerical algorithm to compute off-zenith backscatter from simulated Kelvin-Helmholtz instabilities in the mesospheric region (Franke et al, 2011), and revealed the biases in the obtained Doppler spectra as a function of the stage of turbulence development. Simulation-based approaches like this clearly underpin future investigations of the validity of the partial reflection Doppler techniques employed in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…Following F11, we assume radar backscatter from the life cycle of a KH instability described by an LES description of KH instability evolution for Ri = 0.05, Re = 10 4 , and a Prandtl number Pr = ν / κ = 1. We assume KH and radar parameters appropriate to higher levels of the atmosphere, where effects of humidity can be neglected.…”
Section: Backscatter Environment and Virtual Radar Measurement Paramementioning
confidence: 99%
“…A large Re also allows for rapid breakdown of the KH billows (or cat's eyes) via secondary instabilities arising initially in the billow exteriors that lead to turbulence generation, penetration throughout the billow, shearing of the billows to a horizontally uniform turbulence layer, and eventual restratification as turbulence subsides. Additional details are provided by F11 and references therein. For our simulation, the initial horizontal mean wind is given by U ( z ) = U o tanh ( z / h ), with U o = 5 m s −1 and h = 150 m, such that U z = U / h = 0.0333 s −1 , the KH instability has a most unstable horizontal wavelength L = 12.566 h , and the billow and turbulence layer will approach a typical depth of D ∼6 h ∼900 m and allow radar sampling representative of such measurements in the MLT.…”
Section: Backscatter Environment and Virtual Radar Measurement Paramementioning
confidence: 99%
See 2 more Smart Citations